The Dorsal/miR-1959/Cactus feedback loop facilitates the infection of WSSV in Litopenaeus vannamei. (September 2016) - Xu, Xiaopeng; Yuan, Jia; Yang, Linwei; Weng, Shaoping; He, Jianguo; Zuo, Hongliang
Abstract: miR-1959, a novel microRNA identified from Litopenaeus vannamei, mediates a positive feedback loop between Dorsal and Cactus that can continuously maintain the activation of the NF-κB pathway. It has been known that miR-1959 is involved in antibacterial immunity in shrimp, but its function in antiviral responses is still unknown. In this study, we focused on the role of miR-1959 in infection of white spot syndrome virus (WSSV), the major viral pathogen in shrimp worldwide. The expression of miR-1959 in shrimp hemocytes, gill, and hepatopancreas was significantly up-regulated upon WSSV infection. Dual-luciferase reporter assays demonstrated that miR-1959 could enhance the activity of the promoter of WSSV immediate early gene ie1 . In vivo experiments also showed that inhibition of miR-1959 led to decrease of the mortality of WSSV-infected shrimp and the genome copies of WSSV in tissues, meanwhile the expression of WSSV ie1 and VP28 genes was down-regulated. In contrast, increase of the miR-1959 level in shrimp by injection of miR-1959 mimics produced opposite results. These suggested that the Dorsal/miR-1959/Cactus feedback loop could favor the infection of WSSV in shrimp. Thus, our study helps further reveal the interaction between WSSV and shrimp immune system. Highlights: The expression of miR-1959 is up-regulated during WSSV infection. The Dorsal/miR-1959/Cactus loop regulates the expression of WSSV ie1 gene. The Dorsal/miR-1959/Cactus loop favors the infection of WSSV.